DETERIOTATION IN FISH QUALITY SNAKEHEAD (Channa striata) WITH DIFFERENT LETHAL TECHNIQUE AT ROOM TEMPERATURE 28˚C - Dewi Trisnawati; Rahman Karnila; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study was aimed to determine determine the lethal techniques to maintain the quality of the freshness of snakehead fish for 12 hours. This research was an experiment with a non factorial complete random design. The treatment was used a lethal fish technique consisting of piercing parts of the brain / Medulla oblongata (A1), cold temperatures (A2), and beating (A3). Observations after the fish is turned off by turning off different techniques performed at intervals of 0, 4, 8, and 12 hours on the sensory quality, chemical and microbiological. The analysis parameters were consisted of organoleptic eyes, gills, and odors), chemistry (TVB, glycogen), and total microbes. The results showed that snakehead fish with deadly technique by being stabbed, cold temperature, was produced organoleptic quality (eyes, gills, and odors) from 0-8 hours the quality can still be maintained freshness. The Treatment of A1, on the hour to 12 organoleptic (eyes, gills, and smell) still worth resulting average value 6:00, except treatment A2, and A3, are not worthy for consumption (spoiled). TVB analysis results, during the observation of 0- 12 hours of snakehead fish with different way of death experienced an increase at 8 hours still according of quality standards, the 12th hour TVB snakehead fish value > 25 (spoiled). The lowest glycogen levels in treatment A3, at 4-12 hours instead of A2 and A3. Microbiologically, the treatment of A3 treatment has the highest total microbial value. The best lethal technique is by getting a fish stabbed in a part of the brain that can maintain the freshness of snakehead fish for 12 hours. Snakehead are turned off by plugging in the brain, organoleptic (eyes, gills and smell), chemistry (TVB and glycogen), and the total microbiological according to SNI quality standards for fresh fish.Keywords: glycogen, lethal techniques of fish, organoleptic, TPC, TVB.1)Student